Creativity, or, Holding on to aroha : exploring, exemplifying and encouraging creativity in adulthood : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Adult), Massey University - Grayburn-Moore, Judith (Massey University, 2002)
"Creativity is the sixth sense, transporting us to dreamed of places which the other five cannot reach," to paraphrase the Prime Minister, the Right Honourable Helen Clark. It was the task of this thesis to 'catch' creativity, scrutinise it and make sense of it. Accordingly, it was necessary to: Define creativity as the catalyst for effective innovation Determine who manifests it; major and minor exemplars Discover where it occurs; personal and public sites Detect how it can be effectively encouraged Delve into reasons for esteeming it; philosophical and pragmatic Answers to the above alliterative list's demands, were found in three places: The first was a global location, specifically the international literature on creativity, with particular reference to that written over the past fifty years The second was a New Zealand venue for the encouragement of creativity, The Leaming Connexion, Wellington, evidenced in the story of its founder The third was in the personal perspective of five people who are convinced that creativity is central to shaping how they live. They agreed to be identified as a signature, witnessing the role that creativity has in their lives. Throughout, the theoretical and actual informed each other, as well as the thesis author. Soon universal evidence of creativity's relevance became apparent. On a poetic note, the study concluded that creativity is worth holding onto since it is at the heart of what makes us take nothing for granted. In so doing, its breath grants humanity meaning. More prosaically, the thesis ends with five practical recommendations as to how some of the insights gained might be implemented to help make living and learning more meaningful in an increasingly complex world.
Keywords: Creative ability; Adult education -- New Zealand